INTEGRATED ENGINEERING AND SERVICE TEST OF CONTAINER, WATER, PLASTIC, 5-GALLON. - Baggs, Frank H.; Silber, Michael L.; Brugh, Joseph F.; Coomer, Carroll M.; Parkhurst, Henry A. (1968)
An Integrated Engineering and Service Test of the Container was conducted to determine technical performance and safety characteristics of the container and to determine the suitability of the container for use by the Army. It was concluded that the plastic water container: is not suitable for arctic use; is more suitable than the steel container for tropic and desert use; is suitable for temperate use; and is safe for its intended use. It was also concluded that full plastic containers are suitable for airdrop and internal and external air transport and that the redesigned cap satisfies the requirement to fill canteens without waste of water but it leaks at the air vent. It is recommended that the plastic water container be considered: suitable for use by the U.S. Army in temperate, tropical, and desert environments; not suitable for use in arctic winter environment; and as suitable as the steel container for airdrop and internal and external air transport.